Development of an ac-dc buck-boost power factor correction - Saad, Sahrudin (2013)
Increasing the power quality is a subject which has received increased attention in recent years. Power factor correction (PFC) is one of the power quality points which is receiving greater attention as evidenced by the number of manufacturers which are manufacturing various types of integrated circuits for power factor correction. Nonetheless, Power Factor Correction with AC-DC Buck Boost Converter is still infrequently being used. This project proposes of a development of AC-DC Buck Boost Power Factor Correction to improve the power factor to the near unity (0.99). For this project, the two objectives that have been identified are to develop the design of the ACDC Buck-Boost Power Factor Correction model and to implement the simulation of ACDC Buck-Boost Power Factor Correction. The Matlab Simulink software is used to do the design of the circuit experimented; Circuit without any PFC circuit, Circuit with open-loop PFC circuit and Circuit with closed-loop PFC circuit.. The results conclude that there is improvement of the power factor using the proposed AC-DC Buck Boost Power Factor Correction.